2010
DOI: 10.1097/ico.0b013e3181aebf7a
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Pathogenic Mutations in VSX1 and SOD1 Genes in Patients With Keratoconus

Abstract: The absence of pathogenic mutations in our large number of unrelated patients with KC indicates that other genetic factors are involved in the development of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 18 publications
2
48
0
7
Order By: Relevance
“…In this study, 3 sequence variations were detected, all of which have been previously reported [3,4,18,29,30]. We found the H244R mutation in exon 4 of the gene; it was present in 2% of the patients and 2% of the healthy control subjects, which is concordant with the results of other studies [12,23,31,32,33,34,35,36] (table 3). The H244R variant is important as it is 100% conserved from flies to humans.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, 3 sequence variations were detected, all of which have been previously reported [3,4,18,29,30]. We found the H244R mutation in exon 4 of the gene; it was present in 2% of the patients and 2% of the healthy control subjects, which is concordant with the results of other studies [12,23,31,32,33,34,35,36] (table 3). The H244R variant is important as it is 100% conserved from flies to humans.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the superoxide dismutase isoenzyme 1 encoded by SOD1 located on chromosome 21 was considered an attractive candidate gene because oxidative stress is hypothesised to have a role in the aetiology of KC 57 and there is an increased prevalence of KC in patients with Down syndrome (trisomy 21). 58 Despite the identification of an intronic deletion that segregated with KC in two small families, 58 this finding has not been replicated in additional cohorts, 59,60 and it remains to be established whether variants in this gene are associated with KC. Similarly, other studies have investigated the transcription factor visual system homeobox 1 encoded by VSX1, a gene implicated in posterior polymorphous corneal dystrophy (PPCD), because these PPCD patients have localised steepening of the anterior cornea similar to KC.…”
Section: Geneticsmentioning
confidence: 89%
“…One of these mutations, Gly160Asp, was found in five affected patients with PPD and/or KTCN (one with PPD, three with KTCN and one with both abnormalities). However, to date, none of the subsequent studies, 64,65 including ours, 29 have confirmed a role of changes in either VSX1 or SOD1 gene in the KTCN phenotype.…”
Section: Discussionmentioning
confidence: 99%